MicroRNAs control eyelid development through regulating Wnt signaling. Issue 3 (4th February 2019) - Nagai, Takahiro; Trakanant, Supaluk; Kawasaki, Maiko; Kawasaki, Katsushige; Yamada, Yurie; Watanabe, Momoko; Blackburn, James; Otsuka‐Tanaka, Yoko; Hishinuma, Mitsue; Kitatmura, Atsushi; Meguro, Fumiya; Yamada, Akane; et al.
Abstract : Background: The timing, location, and level of gene expression are crucial for normal organ development, because morphogenesis requires strict genetic control. MicroRNAs (miRNAs) are noncoding small single‐stranded RNAs that play a critical role in regulating gene expression level. Although miRNAs are known to be involved in many biological events, the role of miRNAs in organogenesis is not fully understood. Mammalian eyelids fuse and separate during development and growth. In mice, failure of this process results in the eye‐open at birth (EOB) phenotype.Results: It has been shown that conditional deletion of mesenchymal Dicer (an essential protein for miRNA processing; Dicer fl / fl ; Wnt1Cre ) leads to the EOB phenotype with full penetrance. Here, we identified that the up‐regulation of Wnt signaling resulted in the EOB phenotype in Dicer mutants. Down‐regulation of Fgf signaling observed in Dicer mutants was caused by an inverse relationship between Fgf and Wnt signaling. Shh and Bmp signaling were down‐regulated as the secondary effects in Dicer fl / fl ; Wnt1Cre mice. Wnt, Shh, and Fgf signaling were also found to mediate the epithelial–mesenchymal interactions in eyelid development.Conclusions: miRNAs control eyelid development through Wnt. Developmental Dynamics 248:201‐210, 2019. © 2019 Wiley Periodicals, Inc. Key Findings: miRNAs control eyelid development through Wnt signaling.